Por uma teologia do laicato : uma proposta de articulação entre o empenho secular dos fieis cristãos leigos e o reino de Deus - Steffen, Carlos José Monteiro (2019)
The lay members of Christ’s Faithful People (Christifideles Laici). Doctoral thesis. Ecclesiology. The mission of the Church is to collaborate with the growth of the kingdom of God in the world, under the action of the Holy Spirit, so that men participate in the redemption of Jesus Christ. From the word and the grace of salvation light and strength for the promotion of the dignity of the human person, the transformation of society and the ordination of creation to God (cf. Eph 1, 10, GS 40, AA 2). The fundamental objective is to propose a theological and pastoral reflection on the identity of the vocation of the lay faithful, in the light of the ecclesiology of organic communion. The lay faithful is understood as the ecclesial subject who follows Jesus Christ on the path of the kingdom of God by exercising his secular activities from within the temporal realities in which he is inserted and by which he constitutes his existence (cf. LG 31). The main research method used was the bibliographic research. As a complement to documentary research, a qualitative research was conducted with focus groups. The data of the groups were analyzed through the technique of content analysis, using the program NVivo version 12. The thesis is structured in three parts. In the first two, the data on the identity vocation of the lay faithful are compiled. The last part is organized in three chapters, inspired by the see, judge and act method. Focus group research serves as a pastoral reference. In the second chapter, there is an effort to synthesize all the data collected. Finally, in the last chapter, we present our own contribution on the fundamental question of laity theology: the relation between temporal progress and the kingdom of God (cf. GS 39). The thesis argues that the articulation between the Kingdom of God and the secular commitment of the lay faithful happens through the theological virtues, in view of a future of justice and peace in the world.